Use of ICT and Develepoment of Tourism Sector in Albania - Bekteshi, Luan; Bekteshi, Jonida (European Scientific Journal, ESJ, 2017)
Information and Communication Technology (ICT) is increasingly playing an important role in developing a competitive economy based on knowledge and innovation. Use of ICT enables the provision of a higher quality of citizen’s life; it helps ease and efficiency of business processes and increase the efficiency and transformation of management. The use of ICT in different sectors of the Albanian economy has begun to be realized rapidly, improving economic and financial performance and expanding the range of services that are offered to users. ICT has been used massively also a sector which in Albania brings an important impact on GDP it is the tourism sector, however, it is noted that the use of ICT in this sector is at levels lower than in other countries of Europe as well as the region. The use of ICT and the Internet in the tourism sector in the world but also in Albania has enabled the creation of a new business environment, the global distribution of information as a very important element for the tourism sector and the creation of new channels of distribution, transforming the tourism sector globally. The tourism sector in Albania, which is competing strongly from neighboring countries after the period of its establishment and strengthening, currently faces the challenge of the massive use of ICT in the provision of information and the enhancement of services for its clients. The purpose of this paper is to evidence the level of use of ICT in the tourism sector in Albania, and based on analysis of data collected, presents recommendations on the use of ICT in the sector, aimed at increasing performance, expanding services and improving the quality of services provided to customers.